Pd-catalyzed formal Mizoroki–Heck coupling of unactivated alkyl chlorides - Geun Seok Lee (Nature Portfolio, 2021)
The use of alkyl chlorides in Pd-catalyzed Mizoroki–Heck coupling reactions remains an unsolved problem despite their significant synthetic potential. Here, the authors show that alkyl chlorides can efficiently participate in Mizoroki–Heck cross-coupling reactions with excellent functional group compatibility via photoinduced Pd catalysis.